2000
DOI: 10.1016/s0304-3959(00)00251-7
|View full text |Cite
|
Sign up to set email alerts
|

Tactile allodynia in the absence of C-fiber activation: altered firing properties of DRG neurons following spinal nerve injury

Abstract: We examined the relation between ectopic afferent firing and tactile allodynia in the Chung model of neuropathic pain. Transection of the L5 spinal nerve in rats triggered a sharp, four- to six-fold increase in the spontaneous ectopic discharge recorded in vivo in sensory axons in the ipsilateral L5 dorsal root (DR). The increase, which was not yet apparent 16 h postoperatively, was complete by 24 h. This indicates rapid modification of the electrical properties of the neurons. Only A-neurons, primarily rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
277
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(308 citation statements)
references
References 77 publications
20
277
3
4
Order By: Relevance
“…We selected medium-sized neurons since they include nociceptors, and because they constitute a physiologically relevant cellular population that develops increased excitability after nerve injury [58,80]. Several studies have indicated that this neuronal population exhibits the most significant phenotypic changes after nerve injury [11,23,53,55,56,63,80,98]. Our observations on iberiotoxin-sensitive current in small neurons demonstrates that injury-related effects on primary afferent neurons are not unique to the medium size group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We selected medium-sized neurons since they include nociceptors, and because they constitute a physiologically relevant cellular population that develops increased excitability after nerve injury [58,80]. Several studies have indicated that this neuronal population exhibits the most significant phenotypic changes after nerve injury [11,23,53,55,56,63,80,98]. Our observations on iberiotoxin-sensitive current in small neurons demonstrates that injury-related effects on primary afferent neurons are not unique to the medium size group.…”
Section: Discussionmentioning
confidence: 94%
“…Inhibition of K (Ca) channels by norepinephrine has been also implicated in the membrane hyper-excitability and hyperalgesia after chronic constriction sciatic nerve injury [37]. Spontaneous firing develops also in injured myelinated afferents after SNL [53], thus our findings that axotomized myelinated -but not adjacent uninjured afferents-develop increased excitability, and axotomized medium-sized fibers lose I K(Ca) , contribute additional support to the argument that injured (and not uninjured) myelinated afferents mediate neuropathic pain behavior after SNL [6]. Because BK channels control neurotransmitter release [86] and inter-neuronal glutaminergic synaptic efficacy [72], it is also likely that loss of BK currents in small and medium sized neurons after axotomy may enhance synaptic transmission of afferent signaling, as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinal nerve (stump) was stimulated with a suction electrode. Action potentials were evoked with a fixed latency to a minimum of three stimuli before they were classified according to their conduction velocity: A-␤, Ͼ14 m/sec; A-␦, 1-14 m/sec; C fibers, Ͻ1 m/sec (Waddell et al, 1989;Liu et al, 2000). The neural signal was differentially amplified, filtered (Neurolog, Digitimer, Hertfordshire, UK), displayed on a digital oscilloscope, and digitized as waveforms at a rate of 20 kHz via the Spike 2 data acquisition system (Cambridge Electronic Design, Cambridge, UK) on a Pentium III PC.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the precise etiology, clinical presentation often involves negative (loss-of-function) symptoms, including loss of motor control (i.e., paresis) and sensory deficits such as blindness and numbness, as well as positive (gain-of-function) symptoms, including muscle spasms, tactile allodynia, and chronic pain that is constant or paroxysmal (1,(4)(5)(6)(7). Which muscles or sensory modalities are affected depends on where in the nervous system the demyelinating lesions develop, but changes in conduction velocity alone are clearly insufficient to explain the breadth of symptoms observed, especially the positive ones.…”
mentioning
confidence: 99%